Study of the influence of micellar casein and spelt flour on yoghurt quality indicators - Polishchuk, Galyna; Breus, Natalia; Kochubei-Lytvynenko, Oksana; Osmak (Fedchenko), Tetiana; Semko, Tetiana; Borova, Marina (Study of the influence of micellar casein and spelt flour on yoghurt quality indicators / G. Polischuk, N. Breus, O. Kochubey-Litvinenko, Т. Osmak, T. Semko, M. Borova // EUREKA: Life Sciences. – 2020. – № 4. – P. 44-52., 2020)
The aim of the research is to study the effect of protein-containing ingredients of animal and plant origin on the quality indicators of yoghurt for the scientific substantiation of its recipe composition. Micellar casein and spelled flour are characterized by high nutritional value, exhibit functional and technological properties and can significantly affect the quality indicators of yogurt. To confirm this, the possibility of complete replacement of the structure stabilizer in the composition of yoghurt with micellar casein and spelled flour, both separately and in various ratios, was studied. As a single criterion for optimizing the recipe composition of yoghurt at various ratios between casein and spelled flour, product quality indicators were used: the degree of syneresis, effective viscosity, organoleptic indicators.
Keywords: yogurt; micellar casein; optimization of the composition; йогурт; міцелярний казеїн; оптимізація складу; кафедра технології молока і молочних продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки